Changes in Irish exports (second paper) - Oldham, C.H. (Statistical and Social Inquiry Society of Ireland, 1919)
In a previous Paper (read to this Society on April 26th, 1918) I analysed the figures for the Exports at Irish Ports which have been published by the Department of Agriculture and Technical Instruction for Ireland for the twelve years 1904 to 1915 inclusive. I grouped together those items in the annual Return which were products of the same industry or employment; and I compared the value-changes which have occurred in the principal exporting trades during the twelve years. Since then the Department has issued the Return for the year 1916.
Read Friday, February 14th, 1919
Keywords: Trade growth; Export industry; 314.15